Compact Remnant Constraints on the Core-Collapse Engine. Issue Volume 16:Issue S363(2020) (June 2020) - Fryer, Chris L.
Abstract: The convection-enhanced neutrino-driven supernova engine's success in explaining a myriad of supernova properties has set it as the standard engine behind supernova. However, due to the success of rotationally-powered engines in explaining astrophysical transients like gamma-ray bursts, these engines have been revived as possible drivers of normal supernovae, competing with this standard engine. In this paper, these competing engines, and the constraints placed by compact remnant observations on these engines, are reviewed. We find that, with these constraints, such rotationally-powered engines can explain less than 1% of the current supernova remnants. In addition, we find that the remnant mass distribution can be used to constrain properties of the convection-enhanced neutrino-driven engine, helping astronomers understand the nature of convection in this engine.